Hubungan Antara Status Kesehatan Periodontal DanPrestasi Belajar Pada Siswa Usia 10-12 TahunDi Mim Klaseman Gatak Sukoharjo - Kusumanto, Haris, drg. Edi Karyadi, MM, drg. SE Yuletnawati, MDSc (2016)
Learning achievement is a benchmark by most people in the world are used as a reference in implementing the person's success in learning. There are two factors that affect the learning achievement one of which is internal factors including periodontal tissues. Periodontal tissue disease that affects a person must be treated immediately and require serious medical treatment. If not promptly treated it can affect the person's learning achievement. The aim of this study was to determine the relation between periodontal health status and learning achievement at students aged 10-12 years in MIM Klaseman Gatak Sukoharjo. The method used in this study was observational analytic method with crosssectional approach. The number of respondents were 51 students in MIM Klaseman Gatak Sukoharjo aged 10-12 years. The study was conducted on June 25th 2016. The sampling technique was using total sampling. Respondents were given an explanation about periodontal health status examination later when approving the respondents would sign an informed consent sheet then conducted checks on respondents. Examination in this study were Oral Hygiene Index (OHI), Gingival Index (GI) and Periodontal Chart to determine the periodontal health status. The results showed that there were 29 respondents had gingivitis and 12 respondents had periodontitis. This study tested using Chi Square test and obtained the value of p = 0.000 (p<0.05) to look at the relation between periodontal health status and learning achievement at students aged 10-12 years in MIM Klaseman Gatak Sukoharjo. These data were analyzed using SPSS 20.00 for windows. The conclusion of this study is there is a relation between periodontal health status and learning achievement at students aged 10-12 years in MIM Klaseman Gatak Sukoharjo.